2019
DOI: 10.1126/scitranslmed.aaf7533
|View full text |Cite
|
Sign up to set email alerts
|

Loss of HDAC3 results in nonreceptive endometrium and female infertility

Abstract: Endometriosis is a disease in which tissue that normally grows inside the uterus grows outside the uterus and causes chronic pelvic pain and infertility. However, the exact mechanisms of the pathogenesis of endometriosis-associated infertility are unknown. Epigenetic dysregulation has recently been implicated in infertility. Here, we report a reduction of histone deacetylase 3 (HDAC3) protein amounts in eutopic endometrium of infertile women with endometriosis compared to a control group. To investigate the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 54 publications
3
70
0
Order By: Relevance
“…Epigenetic modifications mainly refer to the DNA methylation and histone modifications, of which histone methylation and acetylation are most studied (Zhou et al, 2011), that aberrant epigenetic modifications may be associated with the progress of endometriosis (Izawa et al, 2013;Forte et al, 2014;Zhang et al, 2017), recurrent miscarriage (Arias-Sosa et al, 2018;Yu et al, 2018), and implantation failure. For instance, HDAC3 is critical for endometrial receptivity, such that loss of HDAC3 caused an impaired decidualization through the abnormal activation of COL1A1/2 genes in humans (Kim and Yoo, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic modifications mainly refer to the DNA methylation and histone modifications, of which histone methylation and acetylation are most studied (Zhou et al, 2011), that aberrant epigenetic modifications may be associated with the progress of endometriosis (Izawa et al, 2013;Forte et al, 2014;Zhang et al, 2017), recurrent miscarriage (Arias-Sosa et al, 2018;Yu et al, 2018), and implantation failure. For instance, HDAC3 is critical for endometrial receptivity, such that loss of HDAC3 caused an impaired decidualization through the abnormal activation of COL1A1/2 genes in humans (Kim and Yoo, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It is thus logical to suggest, based on the results of the present study, that uterine ACKR3 may be responsible of reducing chemokine activity in the pig endometrium towards the establishment of a state of maternal sperm tolerance [92]. By the same line of reasoning, a downregulation of collagen alpha-2 (I) chain (COL1A2) may contribute to prepare the endometrium to the presence of hemi-allogeneic embryos, as it occurs in other species [93,94]. The fact that copulation downregulated β-1,4-galactosyltransferase 1 (B4GALT1) during this period should not be surprising.…”
Section: Discussionmentioning
confidence: 80%
“…A recently published study on mice demonstrated that loss of HDAC 3 in the uterus of mice leads to implantation failures. Interestingly, HDAC 3 is usually the least frequently expressed HDAC in the endometrial tissue [7,10]. In the study, HDAC 3 was shown to be involved in transcription activation of COL1A1 and COL1A2 (collagenase) genes in humans and col1a1 and col1a2 genes in mice [7].…”
Section: Decidualization and Implantationmentioning
confidence: 89%
“…Interestingly, HDAC 3 is usually the least frequently expressed HDAC in the endometrial tissue [7,10]. In the study, HDAC 3 was shown to be involved in transcription activation of COL1A1 and COL1A2 (collagenase) genes in humans and col1a1 and col1a2 genes in mice [7]. Collagenases are involved in endometrial remodelling and trophoblast invasion during implantation [91].…”
Section: Decidualization and Implantationmentioning
confidence: 90%
See 1 more Smart Citation